Molecular Mechanisms of Melatonin in Alzheimer’s Disease: Insights from Network Pharmacology and Molecular Docking - Mohammadi , Shima; Mahakizadeh , Simin; Poorhassan, Mahnaz; Hassanzadeh, Gholamreza (Journal of Contemporary Medical Sciences, 2025)
Objective: This study explores melatonin's potential therapeutic effects on Alzheimer's disease (AD) using computational tools, focusing on its impact on key pathological features of AD. Methods: We assessed ML's pharmacological properties, toxicity, and biological targets, identifying overlaps with AD-related genes. A pharmacological-target-pathology network was developed utilizing the software Cytoscape, and an analysis of protein-protein interactions (PPI) was conducted employing the STRING database. Gene Ontology (GO) and KEGG pathway enrichment analyses were conducted, followed by protein-ligand docking simulations to validate ML's interactions with key targets. Results: ML exhibits favorable ADME properties, good solubility, and the ability to cross the blood-brain barrier, with a generally safe toxicity profile; however, caution is advised regarding neurotoxicity and respiratory toxicity. Our analysis identified 15,564 AD-related genes and 101 ML targets, with 95 shared genes. Key genes in the PPI network include EGFR, PTGS2, ERBB2, and others. GO analysis highlighted processes related to nitrogen compounds, cell proliferation, and membrane functions, particularly in serotonin receptor signaling. Molecular docking revealed ERBB2 as the strongest ML target, suggesting its potential in AD therapy. Conclusions: This study concludes that ML may offer a promising therapeutic approach for AD by targeting multiple pathways and key proteins, such as ERBB2, and modulating biological processes related to neuronal signaling.